2009
DOI: 10.1128/mcb.00015-09
|View full text |Cite
|
Sign up to set email alerts
|

Cell Migration Is Regulated by Platelet-Derived Growth Factor Receptor Endocytosis

Abstract: Cell migration requires spatial and temporal processes that detect and transfer extracellular stimuli into intracellular signals. The platelet-derived growth factor (PDGF) receptor is a cell surface receptor on fibroblasts that regulates proliferation and chemotaxis in response to PDGF. How the PDGF signal is transmitted accurately through the receptor into cells is an unresolved question. Here, we report a new intracellular signaling pathway by which DOCK4, a Rac1 guanine exchange factor, and Dynamin regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 35 publications
2
58
0
Order By: Relevance
“…Like in the case of border cells [28], blocking RTK endocytosis in NIH3T3 fibroblasts causes impaired migration [33]. Of note, internalized PDGFR recycled via Rab11 or Rab4 positive endosomes to the surface of NHI3T3 cells [33], whereas in human fibroblasts the same receptor is predominantly degraded in lysosomes [34]. Consistent with the importance of balanced PDGFR trafficking for cell migration and other processes, it is subject to regulation by kinases and phosphatases.…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 85%
See 2 more Smart Citations
“…Like in the case of border cells [28], blocking RTK endocytosis in NIH3T3 fibroblasts causes impaired migration [33]. Of note, internalized PDGFR recycled via Rab11 or Rab4 positive endosomes to the surface of NHI3T3 cells [33], whereas in human fibroblasts the same receptor is predominantly degraded in lysosomes [34]. Consistent with the importance of balanced PDGFR trafficking for cell migration and other processes, it is subject to regulation by kinases and phosphatases.…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 85%
“…Upon ligand binding, PDGFRb becomes tyrosine phosphorylated enabling its interaction with the adaptor protein Grb2 which recruits DOCK4 and dynamin2 resulting in receptor endocytosis and Rac activation. Like in the case of border cells [28], blocking RTK endocytosis in NIH3T3 fibroblasts causes impaired migration [33]. Of note, internalized PDGFR recycled via Rab11 or Rab4 positive endosomes to the surface of NHI3T3 cells [33], whereas in human fibroblasts the same receptor is predominantly degraded in lysosomes [34].…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 98%
See 1 more Smart Citation
“…Rab11 effectors are also involved in mammalian cell migration (46)(47)(48). More specifically, PDGF receptor-dependent cell migration has been shown to be regulated by endocytosis in a mammalian cell culture assay (49) and the recycling endosome has been indirectly implicated in the regulation of migration guided by the EGFR (47). Given the involvement of the recycling endosome in so many processes, targeting its function to reduce metastasis is unlikely to be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Dock4 was originally identified as a gene disrupted during tumorigenesis (20). Multiple studies in fibroblasts then confirmed that Dock4 is capable of controlling cell migration by transducing several upstream signals, such as Wnt, platelet-derived growth factor, and RhoG, toward activation of Rac1 (21)(22)(23)(24). However, the functional roles of Dock4 in the central nervous system are only beginning to be understood (25)(26)(27).…”
mentioning
confidence: 99%